2019
DOI: 10.1634/theoncologist.2019-0471
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and Predictive Value of Microsatellite Instability, Inflammatory Reaction and PD-L1 in Gastric Cancer Patients Treated with Either Adjuvant 5-FU/LV or Sequential FOLFIRI Followed by Cisplatin and Docetaxel: A Translational Analysis from the ITACA-S Trial

Abstract: Background Patients with high microsatellite instability (MSI) gastric cancer (GC) show improved survival and no benefit or harm from adjuvant and/or perioperative chemotherapy. The role of immune microenvironment in GC is largely unknown. Materials and Methods In the present study, 256 tumor tissue blocks were centrally collected from patients enrolled in ITACA‐S, a randomized adjuvant trial of 5‐FU/LV versus sequential FOLFIRI and cisplatin‐docetaxel. MSI status was assessed by multiplex PCR, inflammatory re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 36 publications
2
34
0
Order By: Relevance
“…A growing body of evidence has revealed that the MSI status in GC is positively correlated with a better survival compared with the MSS counterpart [3,6]. Additionally, due to their intrinsic mutational burden, increased inflammation and expression of immune checkpoints, such as the programmed death-ligand 1 (PD-L1), MSI tumors exhibit promising molecular hallmarks of potential sensitivity to cancer immunotherapy [7,8].…”
Section: Introduction: Msi As a Well-defined Gc Subtypementioning
confidence: 99%
“…A growing body of evidence has revealed that the MSI status in GC is positively correlated with a better survival compared with the MSS counterpart [3,6]. Additionally, due to their intrinsic mutational burden, increased inflammation and expression of immune checkpoints, such as the programmed death-ligand 1 (PD-L1), MSI tumors exhibit promising molecular hallmarks of potential sensitivity to cancer immunotherapy [7,8].…”
Section: Introduction: Msi As a Well-defined Gc Subtypementioning
confidence: 99%
“…In comparison, the post hoc analysis of the ITA-CA-S trial, which included 256 patients, showed that MSI-H status was an independent favorable factor for both DFS and OS in stage II and III GC patients who had received adjuvant or perioperative CT. 24 In the post hoc analysis of the CLAS-SIC trial, which included patients who had been treated with D2 gastrectomy alone or adjuvant CT after D2 gastrectomy, 19 (6.2%) MSI-H patients had received adjuvant CT; 21 had received surgery alone. Disease-free survival was evaluated in groups, and MSI-H was an independent factor for DFS.…”
Section: Discussionmentioning
confidence: 99%
“…In a study aiming at determining the predictive value of MLH1 and PD‐L1 expression for prognosis and response to preoperative chemotherapy in gastric cancer, Hashimoto et al 26 demonstrated that patients with resectable MSI GC, due to loss of mutL homolog 1 (MHL1), exhibit a good prognosis and negative response to fluorouracil‐based chemotherapy. In a similar study, Di Bartolomeo et al 27 showed that MSI status was independently associated with increased disease‐free survival and overall survival in GC patients randomised for an intensive sequential chemotherapy regimen vs fluorouracil/leucovorin monotherapy as adjuvant treatment. It is noteworthy that MSI tumours are also the ones with a better response to current immunotherapies 28 .…”
Section: Response To Immunotherapymentioning
confidence: 91%